Employer Size and Success in Manpower Training Programs for the Disadvantaged : A Dual Labor Market Analysis - Fottler, Myron (Relations industrielles / Industrial Relations, 1974)
Manpower training programs for the disadvantaged in the United States have been shifting in emphasis over time from institutional to on-the-job training. As a result, it has become increasingly important for program administrators to place trainees in the private sector. Yet little is known about employer characteristics whish are conducive or not conducive to a successful experience. The data presented here indicates that larger compagnies are significantly more successful in these programs than are smaller compagnies.